Direct Metal Laser Sintering: A Digitised Metal Casting Technology - Venkatesh, K. Vijay (Springer India, 2013)
Dental technology is undergoing advancements at a fast pace and technology is being imported from various other fields. One such imported technology is direct metal laser sintering technology for casting metal crowns. This article will discuss the process of laser sintering for making metal crowns and fixed partial dentures with a understanding of their pros and cons.